Hydrothermal activity on the CV parent body: New perspectives from the giant Transantarctic Mountains minimeteorite TAM5.29. (19th December 2019) - Nava, J.; Suttle, M. D.; Spiess, R.; Folco, L.; Najorka, J.; Carli, C.; Massironi, M.
Abstract: TAM5.29 is an extraterrestrial dust grain, collected on the Transantarctic Mountains (TAM). Its mineralogy is dominated by an Fe‐rich matrix composed of platy fayalitic olivines and clasts of andradite surrounded by diopside‐jarosite mantles; chondrules are absent. TAM5.29 records a complex geological history with evidence of extensive thermal metamorphism in the presence of fluids at T < 300 °C. Alteration was terminated by an impact, resulting in shock melt veins and compaction‐orientated foliation of olivine. A second episode of alteration at lower temperatures (<100 °C) occurred postimpact and is either parent body or terrestrial in origin and resulted in the formation of iddingsite. The lack of chondrules is explained by random subsampling of the parent body, with TAM5.29 representing a matrix‐only fragment. On the basis of bulk chemical composition, mineralogy, and geological history TAM5.29 demonstrates affinities to the CVox group with a mineralogical assemblage in between the Allende‐like and Bali‐like subgroups (CVoxA and TAM5.29 are rich in andradite, magnetite, and FeNiS, but CVoxA lacks hydrated minerals, common in TAM5.29; conversely, CVoxB are rich in hydrated phyllosilicates but contain almost pure fayalite, not found in TAM5.29). In addition, TAM5.29 has a slightly different metasomatic history, in between the oxidized and reduced CV metamorphic grades while also recording higher oxidizing conditions as compared to the known CV chondrites. This study represents the third CV‐like cosmic dust particle, containing a unique composition, mineralogy, and fabric, demonstrating variation in the thermal metamorphic history of the CV parent body(‐ies).